Penerapan Teknologi 3D Pada Web Berbasis VRML ( Studi Kasus : PT. Plaza Mebel Pekanbaru ) - Rifqi Amal Reza; Meilany Dewi; Mardhiah Fadhli (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Widespread distribution of sales sites (e-commerce) in the world of internet shopping method led to the start switch of spending directly to shopping over the internet. This is because the efficiency of time and effort, as well as various types of products offered sales site. To support the innovation development of the existing site, then designed a web store that is selling virtual reality for the sale of furniture. Virtual modeling to be made include a furniture store that sells a variety of bedroom set, living room set and kitchen set. In this application, store design and type of item in it is presented in three-dimensional images using Virtual Reality Modeling Language. The web page is displayed with a Java Server Page that will be able to link to some other file formats, such as *. Html and *. Wrl. As for the item or cancellation of orders, made interaction with the data items that have been stored in a MySQL database. This application is a web sales can be an alternative option in the concept of online shopping is backed by a quality visual display item in the web and the ease of interaction between the user with the application. Based on a survey of 30 respondents, found that as many as 24 people or 80% of respondents feel comfortable and easy in the process of shopping with this application.Key words: Plaza Mebel, VRML, Three Dimensions, JSP, MySQL